Investigating the perceived impact of multimedia-based children’s literature on autonomous English learning among Indonesian EFL students - Zhafira Ramadhani.F; Leni Marlina (Researcher and Lecturer Society, 2025)
This study explores the perceptions of EFL students at Universitas Negeri Padang toward the use of digital children’s literature—specifically Storynory and Storybooks Canada—as a tool for autonomous English language learning. Drawing on a descriptive quantitative design, the research collected data from 27 students who had used these platforms during their Introduction to Literature course. A structured questionnaire assessed both physical (visual and auditory) and psychological (emotional engagement, motivation, and self-confidence) aspects of digital storytelling. The results revealed consistently positive perceptions across both dimensions, with an overall mean score of 3.44 on a four-point Likert scale. Students reported that the multimedia features of digital stories enhanced their comprehension, motivation, and enjoyment, while also supporting independent learning. However, slightly lower scores related to linguistic self-confidence suggest a need for additional pedagogical support. These findings highlight the potential of digital children’s literature to foster learner autonomy and engagement in EFL contexts and offer insights for educators and curriculum designers seeking to integrate such tools into higher education language instruction.